“I'm Just a Woman Having a Baby”: Negotiating and Resisting the Problematization of Pregnancy Fatness - Parker, George; Pausé, Cat (Frontiers in Sociology, 2018)
This article explores how fat pregnant people construct successful narratives around their pregnancies and birthing. Fat pregnant people are a critical site for the war on fatness; viewed as irresponsible: threatening the health of their pregnancy, and the far-off future of their child. Contemporary knowledge about pregnancy fatness is imbued with longstanding and powerful gendered biomedical discourses that have served to script women’s reproductive bodies as faulty and deviant compared to the masculine ‘norm’ priming them for medical management and control. The problematisation of pregnancy fatness represents a concerning extension of maternal responsibilisation to pregnancy, entangling pregnant women in a politics of preemptive action to secure their children’s future health, all the while denying the socio-political, economic and cultural realities of women’s lives that constrain their ability to do so. Policy and media responses have located both the causes of, and solutions to, the problem of fat pregnancy in women’s individual self-management imploring them to take responsibility for the necessary lifestyle changes needed to reduce the risks posed by their fat bodies to their babies and the health system. This paper extends critical scholarship on the problematisaiton of pregnancy fatness by identifying the importance of understanding not only how women are oppressed by these dominant discourses but also how they are involved in strategies of negotiation and resistance. By creating space for alternate versions and visions, discursive resistance offers a critical means by which individuals can exercise agency by redefining their lives and recovering their harmed identities.